Anticancer Properties and Mechanisms of Singly-Protonated Dehydronorcantharidin Silver Coordination Polymer in a Bladder Cancer Model - Zhou, Changkuo; Wang, Ganyu; Jing, Weiqiang; Tan, Xuejie; Guo, Hu (Frontiers in Pharmacology, 2021)
Bladder cancer is the most common malignant urinary system tumor. Chemotherapy is frequently used as a treatment regimen for patients with bladder cancer; however, new and effective drugs for bladder cancer need to be developed. The present study examined the effects and mechanisms of Ag-SP-DNC, a silver and singly-protonated dehydronorcantharidin complex, on bladder cancer in vitro and in vivo. It was identified that Ag-SP-DNC suppressed cell proliferation and induced apoptosis in bladder cancer cells in vitro, a suppression associated with G0/G1 phase arrest and elevated intracellular reactive oxygen species (ROS) levels. Furthermore, Ag-SP-DNC enhanced the cleaved caspase-3 levels, disrupted the mitochondrial transmembrane potential balance, and induced intracellular calcium overload. The Ag-SP-DNC-induced bladder cancer cell apoptosis was significantly decreased following treatment with a broad caspase inhibitor, zVAD-fmk. In addition, treatment of MB49 tumor-bearing mice with Ag-SP-DNC significantly inhibited tumor growth and decreased the anti-apoptosis and cell cycle promotion protein levels in the tumor. The results of the present study suggested that Ag-SP-DNC elicits a strong anticancer effect against bladder cancer, and can therefore be used as a promising treatment for bladder cancer.